Two new species of feather mites (Acarina: Analgoidea) from the Moustached Warbler, Acrocephalus melanopogon (Passeriformes, Acrocephalidae), in Romania - Constantinescu, Ioana Cristina; Chișamera, Gabriel; Pocora, Viorel; Stanciu, Cătălin; Adam, Costică (Zootaxa, 2013)
Two new species of feather mites Ingrassiella melanopogoni Constantinescu sp. nov. (Xolalgidae) and Trouessartia mironovi Constantinescu sp. nov. (Trouessartiidae) are described from Acrocephalus melanopogon (Passeriformes: Acrocephalidae) from the South-East of Romania. Ingrassiella melanopogoni differs from all species of the genus by having extensions of the posterolateral angles of the prodorsal shield shorter than in other species and not extending to the hysteronotal shield. Trouessartia mironovi is readily distinguished by having an unique combination of characters within the genus: epimerites I are fused in both sexes and epimerites IVa are highly developed in male (coxal fields IV are almost closed).